Pengembangan Model Pembelajaran Inovatif untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa PGSD - Melina Sita Lestari (Journal of Elementary Education Research, 2025)
Language is not merely a system of rules but a social tool deeply embedded in context. In language education, especially for prospective primary school teachers (PGSD students), it is crucial to foster not only grammatical proficiency but also communicative competence, which includes pragmatic and sociocultural awareness. This article aims to explore the integration of sociolinguistic approaches in language learning as an innovative pedagogical model to enhance students' critical thinking and communicative competence. Using a qualitative descriptive method through literature review, this study gathers and analyzes academic documents from reputable databases such as Google Scholar. Thematic content analysis was employed to identify patterns and key concepts. The findings show that implementing sociolinguistic-based learning—such as authentic discourse analysis, role-playing, and discussions on language variation—effectively improves students' understanding of language variation, register, politeness, and contextually appropriate language use. These strategies also foster pragmatic and sociocultural competence. The study concludes that sociolinguistics plays a pivotal role in bridging linguistic knowledge and practical communication skills, thus preparing students for real-world language use in diverse social contexts.